Philosophical Dimensions of Mathematics Learning Problems among Pre-Service Teachers: An Instructional Needs Analysis for Curriculum Design - Erlyka Setyaningsih; Rima Ronika; Ardanafi Setya Difa (Assyfa Learning Journal, 2026)
In higher education, aligning professional disciplinary knowledge with instructional management requires a deep understanding of learners' foundational perceptions regarding the subject matter. This study aims to analyze mathematics learning problems faced by pre-service elementary school teachers (PGMI students) across ontological, epistemological, and axiological dimensions to provide a rigorous instructional needs analysis for pedagogical design. Utilizing a descriptive quantitative approach, data were gathered using a validated and reliable 30-item questionnaire covering these three philosophical dimensions. The descriptive statistical analysis revealed that most students experienced learning problems in the low-to-moderate categories. Crucially, the axiological dimension emerged as the primary source of difficulties (mean = 27.2), followed by the epistemological dimension (mean = 26.3), while the ontological dimension presented the lowest severity (mean = 25.6). These findings indicate that while pre-service teachers possess a baseline understanding of the nature of mathematics, they face significant hurdles in identifying its practical values and utility, leading to procedural rather than conceptual learning. Consequently, this study underscores the necessity for instructional designers and educators to restructure higher education mathematics curricula by embedding meaningful, context-driven, and philosophically integrated instructional management strategies to overcome these instructional barriers